IMPLEMENTASI PAKET TABEL JEASYUI PADA INVENTORY (STUDI KASUS TOKO BANGUNAN UD.TOKOSA) - Gulo, Esa Novedieli; Rachamawati, Yuliana; Andayati, Dina (Jurnal Script, 2015)
ABSTRACTThis research purpose to design and develop an information system so it becomes an inventory applications in internet, as well as optimizing the use of computers and the Internet as a means of data processing. Packet table jasyui implementation is the design and development of the inventory table of UD.TOKOSA with javascript coding, the draft using php and data storage to Mysql and proponent of web design so builded an inventory web at store building of UD TOKOSA . Jquery EasyUI offers a complete collection of the datagrid component, menu of control panel, and dynamic tabs on the web page. Application packets easyui table is capable to processing data goods from the store building of UD.Tokosa, reports in the form of a pdf file and save time in data processing and have shortcomings in terms of the feasibility of the system login and for the development of the next system can be equipped with a data of goods discount which stored in the inventory, barcode of goods to facilitate the transaction process and be added of forecasting process of goods to be stored and sold.Â Keywords : table packet of jeasyui, inventory, UD.Tokosa, web.